Peran Aparat Kepolisian Dalam Memberantas Mafia Tanah Di Kota Palembang - Rusmini, Rusmini; Husnaini, Husnaini (Lex Librum : Jurnal Ilmu Hukum, 2023)
Precious land can help people in various aspects of life, including economic, social, and political. Land is the primary way for Indonesian agricultural communities to find a source of life. Human life depends heavily on the land, so everybody always strives to possess it and master it. This research uses normative juridic methods. It is hoped that the land mafia eradication team can create security and order for the people in terms of ownership and possession of land in the City of Palembang. In order to improve the management of community-owned land and prevent land mafia, the Agriculture Agency must regularly provide education.